Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Bagian Umum Sekretariat Daerah Pemerintah Kabupaten Madiun - Melyssawati Icha Rahayu (Otonomi, 2022)
The purpose of this study was to analyze the effect of training and work motivation on employee performance at the General Section of the Regional Secretariat of the Madiun Regency Government simultaneously and partially. The population and sample in this study were 53 employees who worked in the general section of the Madiun Regency Regional Secretariat. The analytical method used is multiple linear regression analysis. The results showed that: 1) There was a simultaneous influence between the variables of Training and Motivation on the Performance variable in the General Section of the Regional Secretariat of the Madiun Regency Government; (2) There is no influence between the Training variable on the Performance variable in the General Section of the Regional Secretariat of the Madiun Regency Government; (3) There is an influence between the Motivation variable on the Performance variable in the General Section of the Regional Secretariat of the Madiun Regency Government.